Liprobe, a vital dye for lipid aggregates detection in imaging and high-content screens - Vieira, Sandra I.; Nunes da Silva, Raquel; Alves, Mariana; Dias, Roberto A.; Meireles Sousa, Ana M.; Camões, Fatima; Maia, André; Almeida, Mónica; Rocha, João; Silva, Artur M.; Guieu, Samuel (Frontiers in Photonics, 2022)
Pathological lipid accumulation is a hallmark of several metabolic disorders, and detection of lipid aggregates is an essential step for initial diagnosis and drug screening purposes. But low-cost, simple and reliable detection fluorescing probes are not widely available. Here, six push-pull-push dyes were studied, and proved to be highly sensitive to the polarity of the medium, presenting potential to distinguish structures with different hydrophobic indexes. Importantly, in the presence of lipid aggregates their staining specificity highly increased and their fluorescence wavelength blue-shifted. One of the compounds, named Liprobe, was physiologically inert in cells, as shown by mass-spectrometry and metabolic assays. Liprobe was not-toxic to living zebrafish embryos, and able to differentially stain their muscle and bone tissues. In triglycerides (TG) solutions, a high correlation could be observed between Liprobe 558 and 592 nm emissions and the 0-2.5 mg dL-1 TG range. Subsequent confocal and cell-based high content screens (HCS), revealed that this fluorophore was able to selective detect lipid droplets and ceramide loads in normal and Farber’s disease human fibroblasts, respectively. Our results demonstrate that Liprobe is a suitable fluorescing probe for vital staining of lipid aggregates, compatible with a rapid and cheap HCS assays for preliminary diagnosis of Farber’s disease and potentially of other lipidosis.